American by day - Miller, Derek B., 1970- (Houghton Mifflin Harcourt, 2018)
"A gripping and timely novel that follows Sigrid--the dry-witted detective from Derek B. Miller's best-selling debut Norwegian by Night--from Oslo to the United States on a quest to find her missing brother...Chief Inspector Sigrid Ødegård could be basking in the success of her recent mission to save an innocent child who'd gone missing in Oslo, but instead she is reeling from the deadly showdown that preceded that success. She has decided to take some time off from her job and visit her father at the family farm, where she hopes to relax and consider the implications of her role in recent events. Unfortunately her father has other plans for her. "You're going to America," he tells her. Why? To look for her older brother, Marcus. He's missing. And more than that, it seems his disappearance is connected in some way to the death of a woman he loved--an African-American professor named Lydia Jones. A connection now being investigated by a certain Sheriff Irving Wylie ... Like Norwegian by Night, which had "the brains of a literary novel and the body of a thriller" (New York Times), American by Day is both thought-provoking and suspenseful. Through the eyes of the inimitable Inspector Ødegård, Derek Miller offers a refreshingly funny, disturbing, and slyly perceptive vision of American life."--